This Time Was Different: The Global Safe Asset Shortage and Shadow Banking in Socio-Historical Perspective - Photis Lysandrou; Anastasia Nesvetailova (City, University of London, City Political Economy Research Centre (CITYPERC), 2020)
Safe assets and shadow banking are two closely linked phenomena in contemporary finance. The link is loan securitisation: at a time of a global safe asset shortage, it falls on the shadow banking system to help make good that shortage by manufacturing extra quantities of asset backed securities. When these quantities cannot keep up with volume of safe asset demand, the shadow banking system comes under pressure to manufacture the type of complex structured securities that can potentially cause a financial crisis. That potentiality became reality with the great financial crisis of 2007-8. If a further financial crisis of this scale is to be averted, the regulation of the shadow banking system should be informed by an understanding of the contemporary socioeconomic circumstances that continue to cause a global safe asset shortage. This paper attempts to contribute to such an understanding.
Keywords: 330; safe asset; shadow banking; global safe asset shortage; securitisation; great financial crisis